2022
DOI: 10.1155/2022/4512795
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics and Rehabilitation Training Effects of Shoulder Joint Dysfunction in Volleyball Players under the Background of Artificial Intelligence

Abstract: With the development of volleyball technology, the frequent competition, the fierce competition, and the increase of sports load, the requirements for the athletes’ own body, intelligence, combat, heart, and skills are getting higher and higher. Volleyball is one of the most popular sports in the world. It attracts people all over the world with its strong team appeal and its own unique charm. This study mainly discusses the characteristics of shoulder joint dysfunction in volleyball players and the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In addition, while the use of technology in the form of games is cited to have the advantage of increasing a patient's interest in exercise training, and program adherence, 16 thus hastening recovery in the face of an injury, will this approach work as well within the rehabilitation needs of many older adults as it does for younger adults or adolescents? Even if 'games' or other similar remotely delivered directives are beneficial because they encompass the ability to provide for timely results feedback, and may be deemed recreational or entertaining, rather than therapeutic, can those who are recovering from a stroke, surgery, trauma, or are in pain, or have visual impairments and others ably make adjustments to their training plan if unsupported by a knowledgeable provider as proposed by Tang et al, 17 At the same time, even if targeted training with monitoring could help to both detect as well as foster correct rather than unsafe actions, while helping to selectively strengthen those components of muscle that are especially weak, hence further reducing the probability of any repeated injury, is this practical in all cases, for example in the context of hip fracture recovery in the frail elder.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, while the use of technology in the form of games is cited to have the advantage of increasing a patient's interest in exercise training, and program adherence, 16 thus hastening recovery in the face of an injury, will this approach work as well within the rehabilitation needs of many older adults as it does for younger adults or adolescents? Even if 'games' or other similar remotely delivered directives are beneficial because they encompass the ability to provide for timely results feedback, and may be deemed recreational or entertaining, rather than therapeutic, can those who are recovering from a stroke, surgery, trauma, or are in pain, or have visual impairments and others ably make adjustments to their training plan if unsupported by a knowledgeable provider as proposed by Tang et al, 17 At the same time, even if targeted training with monitoring could help to both detect as well as foster correct rather than unsafe actions, while helping to selectively strengthen those components of muscle that are especially weak, hence further reducing the probability of any repeated injury, is this practical in all cases, for example in the context of hip fracture recovery in the frail elder.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is highly important to monitor sports skills during spontaneous physical exercise. Real-time monitoring and analysis of sports skills can effectively identify incorrect actions and provide feedback [13,14]. The use of electronic devices for monitoring sports skills has made it possible to meet people's requirements for the accuracy and safety of spontaneous physical exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%